Enhancing the security of RCIA ultra-lightweight authentication protocol by using random number generator (RNG) technique - Yasear, Shaymah Akram (2015)
With the growing demand for low-cost Radio Frequency Identification (RFID) system, there is a necessity to design RFID ultra-lightweight authentication protocols to be compatible with the system and also resistant against possible attacks. However, the existing ultra-lightweight authentication protocols are susceptible to wide range of attacks. This study is an attempt to enhance the security of Robust Confidentiality, Integrity, and Authentication (RCIA) ultra-lightweight authentication protocols especially with regard to privacy issue. In the RCIA protocol, IDs value is sent between reader and tag as a constant value. The constant value will enable attacker to trace the location of the tag which violates the privacy users. In order to enhance the security of RCIA protocol, Random Number Generator (RNG) technique has been used. This technique relies on generating random numbers in the tag side, based on Bitwise operations. The idea of this technique is to change the IDs of a tag on every query session so that it will not stay as a constant value. The implementation of Enhanced RCIA has been conducted by using a simulation. The simulation provided the ability to show that the operations of RCIA protocol as to compare with the enhanced RCIA. The outcome shows that the enhanced RCIA outperforms existing one in terms of privacy.